Exploring Factors Affecting the Rural Poor’s Access to Resources and Public Services, Thailand - Totum, Boonmee; Tossamas, Pattarapon (Journal of Ecohumanism, 2024)
Public service involves the state’s or administrative department’s operations in matters aimed at meeting the collective needs of all citizens. The objectives of the research were to: 1) study access to resources and public services of the rural poor, 2) examine the factors that affected access to resources and public services, and 3) propose a policy to solve the problems related to access to resources and public services. This study employed a mixed research method. The study population included 7,520 recipients of the state welfare cards. The samples consisted of 379 state welfare cardholders. The key informants made up the 12 subjects, while the 15 participated in a group focus. The following statistics were used: percentage, mean, standard deviation, and multiple regression analysis. Qualitative data were evaluated using content classification and description. The research found that 1) the overall access to resources and public services of the rural poor was high level, 2) political, economic, social, technological, and cultural factors affected access to resources and public services of the rural poor at a high level. The five variables could predict access to resources and public services of the rural poor by 85.40 (R2.40 = 0.854). An error in the prediction was statistically significant at .05 level, and 3) the recommendations were as follows: the state sectors should focus on services and reduce formality as much as possible. Increase opportunities for the poor and their communities, strengthen public-state agency relationships, make technological equipment accessible, and focus on cultural capital-based community strengthening.